Progresivitas Hukum Islam dalam Fikih Perlindungan Anak Perspektif Muhammadiyah - Ahmad Habibi; Norcahyono Norcahyono; Ardi Akbar Tanjung (Institut Agama Islam Negeri Kerinci, 2025)
The high incidence of violence and violations of children’s rights in Indonesia indicates the need to strengthen child protection through a legal approach that is responsive and oriented toward public welfare (maslaḥah). This article aims to analyze the progressiveness of Islamic law in Fikih Perlindungan Anak from the Muhammadiyah perspective, with a focus on the construction of institutional ijtihād by the Majelis Tarjih and Tajdid and the underlying principles of progressive Islamic law. This study employs a qualitative library research design, using a normative-analytical approach and content analysis of the Fikih Perlindungan Anak text and relevant supporting literature. The findings demonstrate that Muhammadiyah’s Fikih Perlindungan Anak represents a progressive formulation of Islamic law through a dynamic and contextual ijtihād paradigm oriented toward maqāṣid al-sharī‘ah. Such progressiveness is reflected in the fiqh’s responses to contemporary child protection issues—including abortion, stunting, children’s civil rights, children in conflict with the law, child marriage, trafficking, and sexual violence—through an integrative dialogue between Islamic normative sources and Indonesia’s positive law. Accordingly, this fiqh constitutes an important contribution to the development of contemporary Islamic law that is humanistic, justice-oriented, and committed to the protection of vulnerable groups.